The external evaluation in Education - Martínez Lobato, Esteban (Avances en Supervisión Educativa, 2007)
Evaluation is an essential condition for any organization to grow and progress. From this outlook, the evaluation of schools as seen in the Organic Act of Education establishes three possible types: diagnosis evaluation, formative evaluation and self-evaluation.It is often -and wisely- stated that the object of school evaluation is the students' assessment. However, is this  the only dimension to evaluate? This misconception of schools and the process of teaching and learning sets aside some very important factors such as teachers, school facilities, parents' concerns, etc.Every school evaluation process must produce a project or an Improvement Plan, which should include a schedule with actions, timetable, people responsible and resources. This project should be developed as a two-sided contract between the Education Authorities and the school itself, with commitment and obligations for both parts.On the other hand, it must be useful to provide some help to students, by starting out some helping devices, since corrective actions can be trusted only when the problems they are meant to solve are strictly and clearly tackled.